PENGARUH BIAYA, FASILITAS, PELAYANAN DAN MEREK TERHADAP PENERIMAAN MAHASISWA BARU PADA UNIVERSITAS MUHAMMADIYAH TANGERANG TAHUN AKADEMIK 2012-2013 - Resy Perwithasari (JMB : Jurnal Manajemen dan Bisnis, 2016)
The purpose of this study is to examine and analyze the influence of costs, facilities, services and brands on the acceptance of new students. The sample in this study were 98-20 students of the 2012-2013 UMT academic year. The analytical tool used is the validity test, reliability test, simple regression and multiple regression. Partial calculation results can be explained that there is a positive and significant influence between costs, facilities, services and brands towards new student admissions, this is indicated by each tcount of each variable X always greater than t table. The results of simultaneous regression testing using the Dolittle Method show that the value of Fcount is greater than the value of Ftable at the standard deviation (α) of 0.05 or 5%. So this shows there is a positive and significant influence between costs, facilities, services and brands together towards the acceptance of new students at Muhammadiyah University Tangerang academic year 2012-2013. In this study also proves that the simultaneous influence of costs, facilities, services and brands on the acceptance of new students at UMT in the 2012-2013 academic year is strong. The better the price is interpreted, the more complete the facilities, the better the service and the better the brand, the more student acceptance at UMT will be.